Pemanfaatan Pekarangan untuk Kebutuhan Gizi Keluarga di Kampong Tanah Bara, Aceh Singkil - Irvan Subandar; Muhammad Jalil; Maulidil Fajri; Aboe B Saidi (LPPM UNINUS, 2022)
The low nutritional intake of the community is one of the factors causing stunting in infants and toddlers. Kampong Tanah Bara is one of the villages in the Gunung Meriah sub-district that has the highest stunting rate. In an effort to meet the nutritional needs of the Kampong Tanah Bara community, it is necessary to empower household yards. ladder to meet the nutritional needs of the family, so it is hoped that the stunting rate can be reduced. Community service activities in Kampong Tanah Bara aim to empower household yards so that they provide benefits in meeting the nutritional needs of families which are expected to have an impact on reducing stunting. The steps or methods implemented in the activities of using yard land are Focus Group Discussion (FGD), counseling, demonstration of nursery houses, verticulture and hydroponic demonstrations, and evaluation monitoring. The implementation of the service went well and according to plan, although there were also obstacles in the implementation of service activities, namely the lack of citizen participation and the condition of the soil in the sandy yard.